From room to roof: How feasible is direct coupling of solar-battery power unit under variable irradiance?. (August 2020) - Astakhov, Oleksandr; Merdzhanova, Tsvetelina; Kin, Li-Chung; Rau, Uwe
Highlights: PV modules directly coupled to batteries under variety of irradiances and loads. High power matching in PV-battery unit for wide range of irradiances and loads. Feasibility for efficient operation for PV-battery without MPPT. Batteries in PV-systems not only a storage but impedance matching element. Abstract: Integration of photovoltaics (PV) with electrical energy storage (battery) is a straightforward approach to turn intermittent power source into stable power supply. Power coupling, or power matching, between PV-device, a battery, and a load is most frequently performed with aid of maximum power point tracking (MPPT) electronics. MPPT electronics provides high flexibility as for PV and load impedances, and irradiance, however, it brings in additional cost, and complexity, power overhead, potential reliability issues, and interference signals. On the other hand, direct coupling via preselection of PV and battery parameters is a simple scalable and highly efficient alternative to MPPT for a specific set of conditions. We explore with modeling how far a directly coupled PV-battery unit can stay power-matched under various conditions, and demonstrate feasibility of excellent power matching over orders of magnitude of irradiance and a wide range of load resistances. Both a PV-harvester in an office room with low irradiance, non-demanding load, and high autonomy, and a PV-system on a roof with high irradiance, demanding load, and partial autonomy, can operate efficiently without MPPT electronics if an appropriate battery is included. This result emphasizes the role of a battery as an impedance matching element besides storage functionality in a directly matched PV-system.